2007
DOI: 10.1021/la060268p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Transport of Water and Neutral Solutes across Nanofiltration Membranes

Abstract: We carry out a detailed experimental and theoretical study of the influence of temperature on nanofiltration performance using the Desal5DK membrane. Experimental results for the permeate volume flux density and rejection of four neutral solutes (glycerin, arabinose, glucose, and sucrose) are presented for temperatures between 22 and 50 degrees C. Solute rejection is modeled using a hindered transport theory that allows us to unveil the crucial role played by changes in the membrane structural parameters (effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…The DMF permeances increased with the increasing temperature, reaching 275 L m –2 h –1 bar –1 at 140 °C. This behavior is mainly due to the reduced viscosity of DMF at higher temperatures but can also be related to changes in the interactions between DMF and PEEK at different temperatures. When we cooled the system to 25 °C and tested the DMF permeation again, the values were similar, suggesting that aging or significant compaction were not present and confirming the robustness of PEEK membranes …”
Section: Resultsmentioning
confidence: 73%
“…The DMF permeances increased with the increasing temperature, reaching 275 L m –2 h –1 bar –1 at 140 °C. This behavior is mainly due to the reduced viscosity of DMF at higher temperatures but can also be related to changes in the interactions between DMF and PEEK at different temperatures. When we cooled the system to 25 °C and tested the DMF permeation again, the values were similar, suggesting that aging or significant compaction were not present and confirming the robustness of PEEK membranes …”
Section: Resultsmentioning
confidence: 73%
“…Moreover, it was reported that the increase in the mass transfer of solute was more significant than that of water with the increase of temperature [ 39 ], which would increase the permeate flux and reduce acid retention. The decrease of acid retention may be also attributed to the increase in membrane pore size caused by the thermal dilation of the polymer in the active layer at higher temperature [ 38 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“… 35,36 In general, the adsorption of water on the pore walls may reduce the effective pore diameter of the membranes. 37 With rising temperature, the adsorption water layer would be thinner and the pore diameter would be larger. Some research results show that the actual pore size of NF membranes is not affected by temperature due to the effective pore diameter being larger for a thinner adsorption water layer.…”
Section: Resultsmentioning
confidence: 99%
“…Some research results show that the actual pore size of NF membranes is not affected by temperature due to the effective pore diameter being larger for a thinner adsorption water layer. 37 On the other hand, the bulk water viscosity and the intrapore viscosity may reduce with the rising temperature. Both effects would endow the NF membrane with a relatively higher flux.…”
Section: Resultsmentioning
confidence: 99%